CFD Simulation of bubble columns: modeling of nonuniform gas distribution at sparger - Rampure, M. R.; Mahajani, S. M.; Ranade, V. V. (Industrial & Engineering Chemistry Research, 2009)
Most laboratory bubble columns are equipped with sieve plate spargers. The sieve plate spargers are known to lead to nonuniform gas distribution. It is important to account for such nonuniform gas distribution at the sparger in the computational model before experimental data collected from such columns are used to fit the model parameters. In this article, such an attempt is made. A detailed, 3D CFD model was developed to simulate unsteady gas-liquid flows in bubble Columns with sieve plate spargers. The sensitivity of the nonuniformity of gas distribution at the sparger with sparger resistance was examined. The model predictions were compared with the experimental data. The developed model and presented results will be useful for Simulating industrial bubble columns.